Mirror, Mirror, on the Wall, Who's the Most Hawkish Central Bank of All - Steven B. Kamin (American Enterprise Institute (AEI), 2023)
This note assesses the relative aggressiveness with which central banks around the world have responded to the post-pandemic surge in inflation. We estimate a "cross-sectional Taylor rule" in which changes in policy interest rates since December 2020 for a range of advanced and emerging market economies are regressed on changes in core CPI inflation and in output gaps. We find that Brazil exceeded the extent of monetary tightening predicted by the estimated Taylor rule by the greatest extent; on the dovish side, Japan exhibited the greatest deviation from prediction. The Federal Reserve's 5 percentage point hike in rates is just a little higher than the 4 3/4 percentage points predicted by the model, while both the European Central Bank and the Bank of England have tightened more than 2 percentage points less than predicted. A key determinant of these deviations from the model's predictions is the level of pre-pandemic inflation: central banks with histories of high inflation (e.g., Brazil) are more likely to over-tighten relative to the model, whereas central banks that had struggled to push inflation up to target (Japan) are more likely to err on the dovish side.
Keywords: 330